Adaptasi dan Properti Psikometrik Alat Ukur Kepribadian HEXACO Versi Indonesia - Aflah Zakinov Irta; Welan Mauli Angguna; Zhafirah Zhafarina Irawan (Jurnal Pendidikan dan Konseling (JPDK), 2023)
The HEXACO model is a framework consisting of six primary personality factors that are present in an individual, and it represents a revision of the Costa-McCrae FFM that was previously established. HEXACO comprises six dimensions, namely honesty-humility, emotionality, extraversion, agreeableness, conscientiousness, and openness to experience. The aim of this study was to adapt the HEXACO measurement tool into the Indonesian language while ensuring that it is valid, reliable, and able to measure personality traits in the Indonesian population. The study involved 139 participants and utilized five stages of adaptation, which included translation, synthesis, back-translation, expert committee review, and pretesting. The psychometric analysis of the measurement items using Confirmatory Factor Analysis revealed that the Honesty-Humility, Emotionality, and Openness dimensions underwent the most item reduction. The Agreableness, Extraversion, and Conscientiousness dimensions, were reduced to approximately five items in each dimension. The agreeableness dimension had the best items, with a factor loading >0.5 significant at T-Value >1.96, whereas the extraversion and conscientiousness dimensions had one to two items that required revision because they had a factor loading at the critical boundary of >0.3.